A Year Into the Pandemic: The Diversity of Experience Amongst People With Severe Mental Ill Health - Peckham, Emily; Spanakis, Panagiotis; Heron, Paul; Crosland, Suzanne; Johnston, Gordon; Newbronner, Elizabeth; Wadman, Ruth; Walker, Lauren; Gilbody, Simon (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic has amplified pre-existing health inequalities and people with severe mental ill health are one of the groups at greatest risk. In this study we explored the effects of the pandemic and pandemic restrictions on people with severe mental ill health during the first year of the pandemic. Methods: We conducted a longitudinal study in a sample of people with severe mental ill health. The inception survey was carried out between July and December 2020. Participants were then re-surveyed between January and March 2021. People were contacted by telephone and invited to take part in the study over the phone, online or by postal questionnaire. Across both waves we asked participants about their physical and mental health, health risk behaviours, wellbeing, loneliness and employment status. Results: 367 people with severe mental ill health completed the inception survey and 249 people completed the follow up. Whilst some people reported no change in their physical (77, 31%) or mental health (60, 24%) over the course of the pandemic 53 (21%) reported a continuing decline in physical health and 52 (21%) reported a continuing decline in mental health. Participants who maintained a daily routine or reported no decline in physical health were found to be associated with no deterioration in mental health (Daily routine OR 2.27, 95% CI1.11-4.64; no reported physical health decline OR 0.54, 95% CI 0.17-0.70). Participants were less likely to be occupationally active in the first phase of the pandemic compared to before the pandemic and in the second phase of the pandemic. However there was no one single experience of people with SMI and similar to studies in the general populations a range of different scenarios was experienced. Conclusions: we observed a series of factors that might amplify pre-existing health inequalities. Health systems should be mindful of this, and should redouble efforts to set in place changes to practice and policy, which can mitigate these inequalities. Examples might include; raising awareness of the importance of ensuring that people with SMI receive an annual physical health check and supporting people to maintain a daily routine.